(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This article examines, classifies, and analyzes the studies and historical works of Western European and Russian scholars concerning the military operations that took place in Afghanistan between 1979 and 1989, as well as the causes and consequences of the outbreak of the war.